Pipistrellus nathusii Keyserling & Blasius 1839 - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2019)
22. Nathusius’s Pipistrelle Pipistrellus nathusii French: Pipistrelle de Nathusius / German: Rauhautfledermaus / Spanish: Pipistrela de Nathusius Taxonomy. Vesperugo nathusii Keyserling & Blasius, 1839, Berlin, Germany. Pipastrellus nathusii appears to be close to the P. kuhlii complex, which includes paraphyletic P. kuhliiand P. maderensis. Monotypic. Distribution. Most of Europe (from Ireland and Iberian Peninsula E to Russia and W Kazakhstan), Turkey, and Caucasus; also on Mediterranean Is such as Crete or Mallorca. Descriptive notes. Head-body 44-54 mm, tail 30-40 mm, ear 10-5-16 mm, forearm 32-2-37-1 mm; weight 6-15-5 g. Fur color of Nathusius’s Pipistrelle changes seasonally, being dark brown or gray brown in winter and reddish in summer. Fur is long and uniformly colored, but venteris slightly paler or more yellowish than dorsum. Proximal one-half of uropatagium is covered by fur. Bare skin is dark brown, snout is short and rounded, and ears are triangular and short, with slender and rounded tragus. Compared with other pipistrelle species, wings of Nathusius’s Pipistrelle are quite long (wingspan 230-250 mm), perfectly adapted for long flights and its migratory behavior. Although not always reliable, a particular wing venation pattern is used as a diagnostic character (cell from elbow to fifth finger clear ly divided). I* is bicuspid, I’ is longer than second cusp of I, canines are considerably large, P? is small but visible above gum, and lower molars are nyctalodont. Chromosomal complement has 2n = 44, FNa = 50, and FN = 54. Habitat. [Lowland to alpine habitats from sea level up to elevations of ¢. 2200 m in the Alps (probably single vagrant individuals). Habitats selected by Nathusius’s Pipistrelle include woodlands, forest edges, wetlands, open areas, and grasslands. In terms offorests, it occurs in deciduous, lowland, riparian, and coniferous forests and urban gardens with isolated trees. It tends to select those habitats surrounding ponds, lakes, or water bodies; thus,it is common in wetlands, ...